2007
DOI: 10.1111/j.1464-5491.2007.02283.x
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy‐associated plasma protein A in a large cohort of Type 1 diabetic patients with and without diabetic nephropathy—a prospective follow‐up study

Abstract: We find PAPP-A to be associated with increased mortality in Type 1 diabetic patients with nephropathy in unadjusted analysis. After adjustment for traditional risk factors, the prognostic value of PAPP-A was no longer significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…In this way, PAPP-A can act as an autocrine/paracrine regulator of IGF action. A clinical study suggested prognostic value of circulating PAPP-A and increased all-cause mortality in type I diabetic patients with nephropathy (Astrup et al 2007). However, it is not known whether this increase in circulating PAPP-A reflected changes in the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, PAPP-A can act as an autocrine/paracrine regulator of IGF action. A clinical study suggested prognostic value of circulating PAPP-A and increased all-cause mortality in type I diabetic patients with nephropathy (Astrup et al 2007). However, it is not known whether this increase in circulating PAPP-A reflected changes in the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…In type 1 diabetic patients with nephropathy, PAPP-A was associated with increased mortality in unadjusted analysis -however, after adjustment for traditional risk factors, the prognostic value of PAPP-A was no longer significant [24] . Concerning HD patients, to date only two studies evaluating the prognostic value of PAPP-A have been available, both of them with a lower number of patients and a markedly shorter follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…In diabetic patients, no difference in PAPP-A levels in DM1 or DM2 and healthy subjects was found (12) and another group did not fi nd its usefulness as a biomarker of carotid atherosclerosis in type 2 diabetics (13) . Conversely, PAPP-A was associated with increased mortality in type 1 diabetic patients with nephropathy but only in unadjusted analysis; after adjustment for traditional risk factors the prognostic value of PAPP-A was no longer signifi cant (14) . PAPP-A was signifi cantly elevated in allergic rhinitis (15) and in asthma and correlated with asthma severity (16) .…”
Section: History Of Papp-a In Laboratory Medicinementioning
confidence: 99%